The Concept of “Perception” in Islamic Philosophy - Seyyed Ebrahim Aghazadeh (Journal of Philosophical Investigations)
This article explores the concept of "perception" (idrāk) in Islamic philosophy, particularly analyzing the contributions of renowned philosophers such as Avicenna (Ibn Sīnā), Suhrawardi (Shaykh al-Ishrāq), and Mulla Sadra in this field. From the perspective of these philosophers, perception is defined as a means of attaining truth, and its methods establish a profound connection between the material and immaterial worlds. Avicenna views perception as a layered process that begins with sensory inputs and culminates in intellectual comprehension. He emphasizes abstraction in perception, whereby individuals, through their rational faculties, can access higher truths. Suhrawardi introduces the concept of "light" (nūr) and "illumination" (ishrāq) as central to perception, asserting that light inherently enables the human soul to directly access truths, rooted in the intrinsic mediation of the epistemic apparatus. Mulla Sadra proposes a dynamic structure of perception, employing the theories of "the primacy of Being" (aṣālat al-wujūd), "the unity of Being" (waḥdat al-wujūd), and "gradation of Being" (tashkīk al-wujūd). This article divides perception into four stages: sensory perception, imaginative perception, estimative perception, and intellectual perception. Ultimately, the article presents perception as a dynamic synthesis of the soul and reality, inviting the reader to reconsider human cognition beyond material limitations. The significance of perception in the advancement of knowledge and the emphasis on metaphysical Being are illuminated through the analyses of Mulla Sadra and the rich tradition of Islamic philosophy. These investigations greatly contribute to understanding the depth of human interaction with the world and provide a deeper comprehension of Being and understanding.